Regional Income Differences in Hungary - A Multi-Level Spatio-Temporal Analysis - Tamas Dusek (European Regional Science Association (ERSA), 2006)
This paper has two aims. Firstly, it provides a number of critical reflections of the existing methods of the examinations of intertemporal change of spatial differences of various socio-economic indicators, mainly the per capita income. Practically there are two types of analysis of spatial differences in income level, namely intercountry and intracountry investigations. The diverse growth rate of spatial income level of various spatial units (regions, countries, provinces, counties etc.) is a historical-statistical fact which refers to an unrepeatable, unique and particular historical situation. The descriptions of the convergence or divergence of various spatial units in various time periods contribute to our historical knowledge, but the "testing of convergence approach" has no theoretical basis. Secondly, the larger part of the paper illustrates many theoretical issues by the help of the Hungarian spatial income data between 1988 and 2004. The analysis has four spatial levels, more than 3000 settlements, 168 small regions (NUTS IV level), 20 counties (NUTS III level) and 7 regions (NUTS II level).
Keywords: 330